Distribuição espaço-temporal e densidade populacional de Holothuria (Halodeima) Grisea (Holothuroidea: Aspidochirotida) na Praia de Bitupitá, Ceará, Nordeste do Brasil - Dias, Ítala Farias (2012)
The species Holothuria grisea, belonging to the Family Holothuriidae, despite being common in Brazilian coast, still has a big gap in relation to its ecological aspects. The aim of this study was to assess temporal variations in abundance, density and population structure of Holothuria grisea, as well as verify their spatial distribution pattern. The study site was the Bitupitá Beach, located in the municipality of Barroquinha - Ceará, distant about 420 km from Fortaleza. The samples were collected during diurnal spring tides in the intertidal zone on a rock shore of Bitupitá Beach during January to December 2011. The methodology was based on a transect perpendicular to the beach with 160 meters long by scoring six points among ten meters. We used a square of 4 m² at each marked point and the Holothuria grisea found in this square were counted, measured and weighed. The abiotic parameters were measured such as salinity, temperature, pH and dissolved oxygen. Analyses of sediment were performance in the rainy season and the dry season of 2011. The spatial distribution pattern found for Holothuria grisea was aggregate. We observed a total of 620 individuals of H. grisea during the study period. Rainfall influenced the abundance of H. grisea, since the rainy season yielded greater abundance compared to the dry season. We found a positive correlation between rainfall and abundance (r= 0.514). The average annual density was 0.54 ± 0.14 ind / m². There was no difference between the mean densities over months or between the wet and dry seasons, this fact can be explained by the spatial distribution of the aggregate population. The average size observed was 12.89 cm ± 2.42 cm frequency unimodal distribution. The average weight was observed ± 30.29 g 90.28 g showing a frequency distribution unimodal. There was a positive correlation between weight and size of the population. This study has contributed to new knowledge in Holothuroidea ecology in tropical waters.